Philosophy for Spiders On the Low Theory of Kathy Acker - Wark, McKenzie 1961- (Duke University Press, 2021)
It's time to recognize Kathy Acker as one of the great postwar American writers. Over the decades readers have found a punk Acker, a feminist Acker, a queer Acker, a kink Acker, and an avant-garde Acker. In Philosophy for Spiders, McKenzie Wark adds a trans Acker. Wark recounts her memories of Acker (with whom she had a passionate affair) and gives a comprehensive reading of her published and archived works. Wark finds not just an inventive writer of fiction who pressed against the boundaries of gender but a theorist whose comprehensive philosophy of life brings a conceptual intelligence to the everyday life of those usually excluded from philosophy's purview. As Wark shows, Acker's engagement with topics such as masturbation, sadism, body-building, and penetrative sex are central to her distinct phenomenology of the body that theorizes the body's relation to others, the city, and technology